The Economic Impact of Digital Tax Regulation on Indonesian MSMEs - Qurtubi Al Faruq (The Indonesian Journal of Economic Analysis of Law, 2026)
The rapid expansion of the digital economy has prompted governments worldwide to develop tax regulations that ensure fiscal sustainability while supporting business growth. In Indonesia, digital tax policies increasingly affect micro, small, and medium enterprises (MSMEs), which constitute a major pillar of national economic development. This study analyzes the economic impact of digital tax regulation on Indonesian MSMEs through the perspective of economic analysis of law. Employing a normative-empirical approach, the research evaluates the effectiveness of digital tax policies in balancing revenue generation, regulatory compliance, and business competitiveness. The findings reveal that digital tax regulations contribute to increased tax transparency and broaden the tax base, thereby supporting government revenue objectives. However, compliance costs, limited digital literacy, and administrative complexities disproportionately affect smaller enterprises. These challenges may reduce operational efficiency and discourage participation in formal economic activities. The study further demonstrates that legal certainty and regulatory simplicity play crucial roles in minimizing compliance burdens and promoting voluntary tax compliance among MSMEs. Effective digital tax governance requires adaptive regulations that reflect the diverse capacities of business actors within the digital marketplace. The research argues that proportional regulatory frameworks, combined with technological support and tax education initiatives, can improve both economic efficiency and tax compliance. The study concludes that a balanced digital taxation system should simultaneously achieve fiscal objectives and facilitate sustainable MSME growth. These findings provide policy recommendations for developing an inclusive digital tax regime that enhances economic productivity while maintaining regulatory effectiveness in Indonesia’s evolving digital economy.